2009
DOI: 10.1002/aoc.1505
|View full text |Cite
|
Sign up to set email alerts
|

UV–visible spectroscopy for zirconocene activation by MAO in olefin polymerization: activity versus wavenumber

Abstract: Activation of ansa-zirconocenes of the type Rac [Zr{1-Me 2 Si(3-R-(η 5 -C 9 H 5 ))(3-R -(η 5 -C 9 H 5 ))}Cl 2 ] [R = Et, R = H (1); R = Pr, R = H (2); and R = Et, R = Pr (3), R, R = Me (4) and R, R = Bu (5)] by MAO has been studied by UV-visible spectroscopy. Compounds 1-3 have been tested in the polymerization of ethylene at different Al : Zr ratios. UV-vis spectroscopy was used to determine a correlation between the electronic structures of (1-5) and their polymerization activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The most part of authors who studied the UV and visible spectra of the metallocene catalytic polymerization systems [5,12] indicated that the products (1) and (2) were formed at room temperature rapidly (within less than 5 min). The slow formation of these products in the case of the Cp 4 Zr-MAO system (the absorbance maximum is achieved in 50-60 min at 60°C, see Fig.…”
Section: Spectra Of the Cp 4 Zr-mao System In The Uv And Visible Rangesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most part of authors who studied the UV and visible spectra of the metallocene catalytic polymerization systems [5,12] indicated that the products (1) and (2) were formed at room temperature rapidly (within less than 5 min). The slow formation of these products in the case of the Cp 4 Zr-MAO system (the absorbance maximum is achieved in 50-60 min at 60°C, see Fig.…”
Section: Spectra Of the Cp 4 Zr-mao System In The Uv And Visible Rangesmentioning
confidence: 99%
“…It was found [12] that the bathochromic shift in the electronic spectra of the studied metallocene catalytic systems for olefin polymerization was proportional to their activity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation